Rhetorical Techniques in the Negotiation Process - Balova, Stoyanka (Media and Language, 2020)
This article analyzes basic verbal techniques and strategies in political and business negotiations. Negotiations can take place differently. A universal recipe for negotiating behavior cannot be stated. In summary, it is worth mentioning that negotiations that are pragmatic when the parties are not digging into their own positions but looking for alternative options and applying compromise options are positive. In order for negotiations to be successful, several basic rules relating to advance preparation must be observed. There is a need to carefully diagnose the situation, determine the negotiator’s goals, and assess the goals of the other party.